Uji Formulasi Sediaan Salep dari Ekstrak Etanol Daun Salam (Sysygium polyanthum) terhadap Bakteri Staphylococcus epidermidis - Rindi Permata Sari; Yovi Pranata; Putu Nila Sari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Acne (Acne vulgaris) is one of the most common skin problems, affecting 80–85% of adolescents aged 15–18 years, with some cases persisting into adulthood. One of the associated bacteria is Staphylococcus epidermidis, a normal skin flora that can become an opportunistic pathogen. Bay leaves (Syzygium polyanthum) are known to contain secondary metabolites such as alkaloids, flavonoids, tannins, saponins, and essential oils with antibacterial activity. This study aimed to formulate ethanol extract of bay leaves into ointments with concentrations of 10%, 20%, and 30%, test their antibacterial activity against Staphylococcus epidermidis using the disc diffusion method, and evaluate their physical quality (organoleptic properties, homogeneity, pH, adhesion, and spreadability). Results showed that the ethanol extract of bay leaves contained alkaloids, flavonoids, saponins, and tannins. The ointments met topical quality standards with pH 5.8–6.9, adhesion time 36–41 seconds, and spreadability 6.9–8.1 cm. Antibacterial activity increased with higher concentrations: 7.8 mm (10%), 12 mm (20%), and 15 mm (30%), although still lower than the positive control (clindamycin, 34 mm). In conclusion, ethanol extract of bay leaves has potential as an active ingredient in topical anti-acne ointments, but further studies with higher concentrations, in vivo testing, and optimized formulations are needed to achieve efficacy comparable to synthetic antibiotics.